The significance of service quality on customer loyalty with corporate image and customer satisfaction as mediators - Maria Aletta Dei Hariyanto; Dudi Anandya (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2021)
This study seeks to reveal the effect of service quality on customer loyalty mediated by corporate image and customer satisfaction at restaurant X in Surabaya. Data were collected using a questionnaire for each variable, on 150 subjects with the characteristics of a minimum age of 19 years, and a minimum education of senior high school. Data were collected and analyzed using the SEM method with the help of SPSS AMOS 21 software. The results showed that service quality has an influence on customer satisfaction, through corporate image, which in turn affect customer loyalty. Corporate image mediator is fully functional because there is no direct relationship between service quality and customer satisfaction. This shows that consumers feel satisfied not directly caused by service quality, but good service quality form a positive corporate image which then make consumers feel satisfied, ultimately affecting loyalty.